Soluble uric acid primes TLR-induced proinflammatory cytokine production by human primary cells via inhibition of IL-1Ra. Issue 4 (3rd February 2015) - Crișan, Tania O; Cleophas, Maartje C P; Oosting, Marije; Lemmers, Heidi; Toenhake-Dijkstra, Helga; Netea, Mihai G; Jansen, Tim L; Joosten, Leo A B
Abstract : Objectives: The study of the proinflammatory role of uric acid has focused on the effects of its crystals of monosodium urate (MSU). However, little is known whether uric acid itself can directly have proinflammatory effects. In this study, we investigate the priming effects of uric acid exposure on the cytokine production of primary human cells upon stimulation with gout-related stimuli. Methods: Peripheral blood mononuclear cells (PBMCs) were harvested from patients with gout and healthy volunteers. Cells were pretreated with or without uric acid in soluble form for 24 h and then stimulated for 24 h with toll-like receptor (TLR)2 or TLR4 ligands in the presence or absence of MSU crystals. Cytokine production was measured by ELISA; mRNA levels were assessed using qPCR. Results: The production of interleukin (IL)-1β and IL-6 was higher in patients compared with controls and this correlated with serum urate levels. Proinflammatory cytokine production was significantly potentiated when cells from healthy subjects were pretreated with uric acid. Surprisingly, this was associated with a significant downregulation of the anti-inflammatory cytokine IL-1 receptor antagonist (IL-1Ra). This effect was specific to stimulation by uric acid and was exerted at the level of gene transcription. Epigenetic reprogramming at the level of histone methylation by uric acid was involved in this effect. Conclusions: In this study we demonstrate a mechanism through which high concentrations of uric acid (up to 50 mg/dL) influence inflammatory responses by facilitating IL-1β production in PBMCs. We show that a mechanism for the amplification of IL-1β consists in the downregulation of IL-1Ra and that this effect could be exerted via epigenetic mechanisms such as histone methylation. Hyperuricaemia causes a shift in the IL-1β/IL-1Ra balance produced by PBMCs after exposure to MSU crystals and TLR-mediated stimuli, and this phenomenon is likely to reinforce the enhanced state of chronic inflammation.